Bushido Values in The Movie : Rurouni Kenshin: The Beginning (2021) and The Last Samurai (2003) - Muhammad Febri Aviv Fad'li (Metaphor, 2023)
This study is aimed to analyze : (1) The bushido values of samurai presented in the movie “Ruroini Kenshin : The Beginning (2021) and The Last Samurai (2003)”,(2) The transitions of bushido values reflected in the movie “Ruroini Kenshin : The Beginning (2021) and The Last Samurai (2003)”. The study uses descriptive qualitative method to analyzed the film entitled “Ruroini Kenshin : The Beginning (2021) and The Last Samurai (2003)” as the objective research. The collecting data of the research method includes watching and reading, identifying, classifying, and selecting. The analyzing data of the research method by used displaying, explaining, and interpreting. The result of the study : (1) The bushido values of samurai presented in the film “Rurouni Kenshin: The Beginning" (2021) include courage, loyalty, politeness, and honor. While the bushido values presented in the film “The Last Samurai (2003) include honor, loyalty, courage, discipline, honesty, and politeness. (2)The transitions of Bushido values reflected in the films “Rurouni Kenshin: The Beginning" (2021) and "The Last Samurai" (2003) were found in the differences between armor, military weapons, battle mentality, differences in government policies, and the war tactics.